(untitled) (Conferencea, 2024)
The rapid social, economic, political, and ideological changes of today’s world have profoundly impacted the worldview, spirit, and moral development of youth. The evolving global context emphasizes the need for young people to understand their identity, embrace national values, and enhance their intellectual and moral capacities. This article explores the importance of synergetic approaches to education and upbringing, focusing on the integration of national heritage, the ideological framework of the New Uzbekistan, and the development of critical thinking skills to navigate external challenges. It emphasizes the role of intellectual potential and the revitalization of spiritual inheritance in preparing youth to meet the demands of the modern world. Through an examination of educational reforms, societal shifts, and synergetic educational methods, the paper argues for the essential role of intellectual and spiritual development in ensuring the future success of the youth in Uzbekistan.